Exodus 1947 - Holly, David C. (Annapolis, Md. : Naval Institute Press, 1995)
A biography of a ship, with the focus on its final assignment, a desperate race to Palestine carrying 4,500 Holocaust survivors fleeing Europe. it examines the people and organizations at work preceding the birth of Israel, including the haganah, which rescued the ship from the scrap heap for its most important voyage. this episode was but one example of a means of bringing people to the homeland, in keeping with zionist goals.
Includes bibliographical references (pages 225-232) and index.
Keywords: Exodus 1947 (Ship); Exodus 1947 (Ship); Jewish refugees -- Palestine; Emigration and immigration; Jewish refugees; Jewish refugees -- Eretz Israel; Palestine -- Emigration and immigration; Middle East -- Palestine